A novel fibrinogen γ chain frameshift deletion (c.637delT) in a patient with hypodysfibrinogenemia associated with thrombosis - Ivaškevičius, V.; Thomas, A.; Biswas, A.; Ensikat, H.; Schmitt, U.; Horneff, S.; Pavlova, A.; Poetzsch, B.; Oldenburg, J. (Hämostaseologie, 2015)
Inherited fibrinogen (FG) disorders are rare and result in quantitative or/and qualitative FG deficiency. While the majority of patients with clinically relevant FG deficiencies demonstrate a bleeding phenotype, a subset of patients are at increased risk of thrombosis.We report a 54-years old man presenting with a thrombophilic phenotype characterized by two episodes of unprovoked venous thrombosis and a deep vein thrombosis several weeks after myocardial infarction. Recently, he developed A. carotis communis thrombosis and died. Coagulation tests were done using standard procedures. FG genes were screened using direct sequencing. Effect on fibrin clot structure was analyzed by scanning electron microscopy (SEM) and FG chain polymerization was analysed using SDS-PAGE.While thrombophilia testing was negative, we found a decreased concentration of clottable FG (126-148 mg/dl) compared to FG antigen (182-194 mg/dl of normal). The thrombin time was slightly prolonged, while aPTT and reptilase time were within the normal range. A novel deletion in FGG gene (c.637delT) resulting in a frameshift and the premature termination of the γ chain at amino acid position p.228 was identified. SDS-PAGE showed a time-shift in γ-γ and α-α cross linking. SEM showed no statistically significant differences between the patient´s and a healthy control´s fibrin clot structure.In addition to the reduction of FG concentration expected by the nature of the mutation also a functional defect (hypodysfibrinogenemia) was found. Moreover this mutation seems to increase the risk of thrombosis warranting long term anticoagulation possibly in a combination with antiplatelet drugs.
Keywords: Fibrinogen; FGA; FGB; FGG; deletion; thrombosis